VASCULAR EPIPHYTE COMPONENT OCCURING IN URBAN TREES - Fabricante, Juliano Ricardo (2015)
Epiphytes are plants cropped in other plants to damage them. The main characteristics of this group of plants is unknown in this part of Brazil, making it important to study this subject. The aim of this work was to characterize the structural and the floristic composition of vascular epiphytes on urban trees; to classify ecological categories species, according to hoist and to calculate community diversity. The studied area (Professor Jose Inacio Square), standed at the municipal district of Piratininga, Sao Paulo State. The climate is Cwa according to Köeppen classification and sandy phase dark red oxisol (latosol). It had been identified 10 species encompassing 6 gender and 6 families, being with best improvement the Bromeliaceae, representing 30 % of data. Tillandsia, with 3 species, was the most abundant gender and featured holoepiphytes were represented, with 70% species. About epiphyte community structure: Tillandsia recurvata and Tillandsia tricholepis were the most important (with bigger VIe) in the studies community. Diversity was 2.371 nats/individual to specie and 2.04 nats/individual per family. The small number of species and low diversity index should be due to local conditions, urban area, with different features from that founded at normal eco-systems.